Utility of the Occupation-Centered Intervention Assessment for Occupational Therapy Level I Fieldwork - Frigo, Nora; Hanneman, Emiliy; Kashale, Adrianne; Sutton, Margaret; Wright, Erin; Jewell, Vanessa D (International Journal of Practice-based Learning in Health and Social Care, 2019)
This study examined the utility of the Occupation-Centered Intervention Assessment (OCIA) among occupational therapy students and their perceptions of the use of an occupation-centered approach to design interventions during level I fieldwork. Twenty-five students completed training on the OCIA, used the tool on level 1 fieldwork, and then completed a post-test survey containing closed and open-ended questions. Content analysis was used to analyze open-ended questions. Descriptive statistics was used to analyze quantitative data. Overall, students (N = 25) found the OCIA to be a beneficial tool to utilize during fieldwork experiences to recognize and develop interventions from an occupation-centered approach. Currently the Occupational Therapy Practice Framework and models of practice are the primary tools available for student reflection for intervention design. The findings of this study supported the need for a reflection tool to aide in the development and implementation of occupation-centered reasoning during fieldwork experiences.